جريمة الاتجار بالبشر وارتباطها بالهجرة غير الشرعية - قنوع, نزار; خربوط, مجد; طيبا, سـحر أحمد (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يتناول البحث قضية جريمة الاتجار بالبشر التي تعدّ من أهمّ القضايا المعاصرة بالنسبة لدول العالم جميعها، لما تتضمنه من سلبيات الاستغلال الجسدي للأطفال والنساء على مدار التاريخ البشري، منذ عهود الرق والعبيد. والتنبه إليها في الوقت الحاضر يعدّ نتيجةً طبيعيةً للفكر الإنساني الذي تقدّم وتطوّر كثيراً. وقد تطرّق البحث إلى التعريف بالجريمة، وصولاً لإدراك الرابط بينها وبين الهجرة غير الشرعيّة، وتقديم بعض المقترحات التي من شأنها أن تسهم في الحدّ من الجريمة،ومن أهمّ هذه المقترحات: 1- ضمان احترام حقوق الإنسان وحرياته الأساسية كافة وحمايتها. 2 - العناية بموضوع الأمن الإنساني للمرأة بجوانبه كافة ، لاسيّما فيما يتعلق بمنع حالات الاتجار بالنساء ومعاقبتها، أو إجبارهن على ممارسة أعمال البغاء. 3 - تعزيز ثقافة النوع الاجتماعي ونشرها على المستويات والمؤسسات كافة ،وجعل القوانين والسياسات والممارسات الوطنية والمؤتمرات تتفق في مضمونها العام والخاص مع الالتزامات الدوليّة المتعامل بها. This research deals with a study of an issue which is one of the most important contemporary issues for all countries in the world. This issue is the crime of trafficking in human beings because of what it contains of the negative aspects, including physical abuse of children and women throughout human history, since the eras of slavery and the slave, in different ages in the past. Paying attention to them now is a natural result of the most prestigious and progress human thought. The research mentions the definition of this crime in order to understand the link between it and the illegal immigration and provides some suggestions that would contribute to its the reduction. The most important suggestions are the following: 1- To ensure respect for human rights and all fundamental freedoms and protect them. 2-Taking care of the subject of human security for women in all its aspects, particularly with regard to the prevention and punishment of cases of trafficking in women or forcing them to exercise acts of prostitution. 3- The promotion and dissemination of the culture of social gender at all levels, and institutions, and making laws and national policies, practices and conferences agree on its content and public sectors with international obligations traded.